Hacia la aventura de un periodismo creativo: propuesta audiovisual de periodismo de viajes. - Barreto Escudero, Orlando Xavier (MACHALA, 2019)
In recent decades, the term travel journalism, traveling journalism or tourism journalism, has been gaining ground as a specialization within the field of journalism, and has allowed stories to be told using literary and journalistic resources such as news, documentaries and documentaries. the rest. Considered as the fuel of journalism, according to Tejedor (2018) by its very nature of entering the trip, as a tool to tell what has been seen or experienced through different platforms; This specialization has its background in the travel chronicle. This new branch of journalism is used as a strategy to potentialize tourist attractions in a region, making use of traditional or digital media, according to Ruibal (2009), "the birth and displacement of tourist flows towards these attractions", then we could say that tourism requires journalism to reach more countries and more travelers, and on the other hand journalism needs to promote tourism to extend its noble contribution to the development of a region, as long as this travel journalism does not limit itself to exploring the part commercial and business, but more linked to geographical aspects, culture, sociology, etc. (Jané, 2002). In this context, the present research work aims to characterize travel journalism as a journalistic specialization in the production of audiovisual communication products, for which the point of view of several authors related to the subject was analyzed through the technique of analysis of scientific documents, which allowed to have a clearer focus on this branch of journalism that is the basis of this research. The aim was also to determine the relationship between travel journalism and its impact on cultural tourism in the province of El Oro, a point that could be established thanks to the exchange of experiences with experts related to the subject of audiovisual production, journalistic production and journalism. travel through in-depth interviews, which allowed us to understand that this branch of journalism is a field to explore and the perfect combination of journalistic research, travel as a tool and audiovisual production techniques are the perfect ingredients for the production of audiovisual tourism products of quality, therefore this information compiled with this technique also contributed significantly in the theoretical foundation of the proposal. In a third phase of this research the level of audiovisual production was analyzed, under the trend of travel journalism in the province of El Oro aimed at promoting cultural tourism, an objective that was contrasted with an analysis of content of traditional media and relevant digital and interviews with experts in which it was possible to determine that the province of El Oro is still a potential market and that this type of products still has a high demand. Likewise, the qualitative techniques applied in this research in the first three phases contributed significantly to fulfilling the main objective: Design a proposal for an audiovisual product based on travel journalism, which allows potentiating cultural tourism in the Province of El Oro, which it can be disseminated through traditional or digital media and evidencing a work of quality investigative journalism.
En las últimas décadas el término periodismo de viajes, periodismo viajero o periodismo turístico, ha ido ganando terreno como una especialización dentro de la rama del periodismo, y ha permitido contar historias haciendo uso de recursos literarios y periodísticos como la crónica, reportajes, documentales y demás. Considerado como el combustible del periodismo, según Tejedor (2018) por su misma naturaleza de incursionar el viaje, como herramienta para contar lo visto o lo vivido a través de diversas plataformas; esta especialización tiene sus antecedentes en la crónica de viajes. Esta nueva rama del periodismo es utilizada como estrategia para potencializar atractivos turísticos de una región, haciendo uso de los medios de comunicación tradicionales o digitales generando según Ruibal (2009)“el nacimiento y desplazamiento de corrientes turísticas hacia esos atractivos”, entonces se podría decir que el turismo requiere del periodismo para llegar a más países y más viajeros, y por otro lado el periodismo necesita fomentar el turismo para ampliar su noble contribución al desarrollo de una región, siempre y cuando este periodismo de viaje no se limite a explorar la parte comercial y empresarial sino que se vincule más a aspectos geográficos, cultura, sociología, etc.(Jané, 2002). En este contexto el presente trabajo de investigación tiene como finalidad en la fase teórica caracterizar el periodismo de viajes como especialización periodística en la producción de productos comunicacionales audiovisuales, para lo que se analizó el punto de vista de varios autores relacionados al tema mediante la técnica de análisis de documentos científicos, lo que permitió tener un enfoque más claro sobre esta rama del periodismo que es la base de esta investigación. Así también se buscó determinar la relación entre el periodismo de viaje y su incidencia en el turismo cultural de la provincia de El Oro, punto que pudo ser establecido gracias al intercambio de experiencias con expertos relacionados al tema de producción audiovisual, producción periodística y periodismo de viajes mediante entrevistas a profundidad, lo que permitió comprender que dicha rama del periodismo es un campo por explorar y la combinación perfecta de la investigación periodística, el viaje como herramienta y las técnicas de producción audiovisual son los ingredientes perfectos para la producción de productos audiovisuales turísticos de calidad, por lo tanto esta información recopilada con esta técnica también contribuyó significativamente en la fundamentación teórica de la propuesta. En una tercera fase de esta investigación se analizó el nivel de producción audiovisual, bajo la tendencia del periodismo de viaje en la provincia de El Oro orientados a fomentar el turismo cultural, objetivo que puso contrastarse con un análisis de contenidos de medios de comunicación tradicionales y digitales pertinentes y entrevistas con expertos en los que se pudo determinar que la provincia de El Oro aún es un mercado en potencia y que todavía este tipo de productos tiene una alta demanda. Así también las técnicas cualitativas aplicadas en esta investigación en las tres primeras fases contribuyeron significativamente a cumplir el objetivo principal: Diseñar una propuesta de un producto audiovisual basado en el periodismo de viaje, que permita potencializar el turismo cultural en la Provincia de El Oro, que puede ser difundido a través de medios de comunicación tradicionales o digitales.y que evidencian un trabajo de periodismo investigativo de calidad.
Keywords: PERIODISMO; TURISMO; CRONICA